The Role Of Digital Payment Mediation In The Adoption Of Digital Technology To Improve The Performance Of MSMEs In Tuban Regency - Nara Dea Atha Raya; Achmad Kautsar; Nanang Hoesen Hidroes Abbrori; Muhammad Fajar Wahyudi Rahman (CV. AFDIFAL MAJU BERKAH, 2026)
Objective – This study aims to analyze the effect of technology adoption on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Tuban Regency and to examine the role of digital payment as a mediating variable in this relationship. The adoption of digital technologies and payment systems is expected to improve transaction efficiency, accelerate cash flow, and enhance financial transparency, which may ultimately improve MSME performance. Design/Methodology/Approach – This study uses a quantitative research design with a survey approach involving MSME actors in Tuban Regency. Data were collected through questionnaires distributed to MSME owners and managers. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the direct and indirect relationships between technology adoption, digital payment usage, and MSME performance. Findings – The results show that technology adoption has a positive and significant effect on MSME performance. In addition, technology adoption significantly influences the use of digital payment systems. Digital payment also has a positive and significant effect on MSME performance and acts as a mediating variable that strengthens the relationship between technology adoption and MSME performance. Implications – The originality of this study lies in examining the mediating role of digital payment in the relationship between technology adoption and MSME performance within the context of local MSMEs in Tuban Regency. The findings provide theoretical contributions to digital technology adoption research and practical implications for policymakers and MSME stakeholders in encouraging digital transformation to improve competitiveness and sustainability in the digital economy.